PERANAN HAKIM DALAM PENEGAKAN HUKUM DI INDONESIA - Abdul Kholiq (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2018)
Judge is one of the elements of law enforcement, therefore the judge is very important role in law enforcement, that is checking, hearing and ultimately decide the case submitted to him freely and independently without any influence from anywhere. In law enforcement is influenced by several factors, namely legal factors, law enforcement, facilities and infrastructure, society and culture.